Analysis Of Citizenship Rights And Mixed Marriages Between Rohingya Refugees And Indonesian Citizens (WNI) - Mirsa Astuti; Rizka Syafriana; Ramlan (Faculty of Law, Universitas Pekalongan, 2025)
Indonesia has come under fire at home and abroad for its rejection of Rohingya refugees, making it irresponsible to accept refugees in its territory. There is no clear legal umbrella in Indonesian law for marriage between Indonesian citizens and refugees. This can be seen from the fact that Article 57 of the Marriage Law only regulates marriage between Indonesian citizens and foreigners who have citizenship status, there will also be discussed in this study regarding the mixed marriage status of Rohingya refugees and the legal status of children born from mixed marriages, This research method uses a qualitative approach carried out by collecting data both in initial observations and during the research, Solving the Rohingya problem regarding the legal status of children born from mixed marriage can only be done if all parties have a strong commitment to side with the values of morality and humanity by taking concrete steps in resolving the root of the problem, so that the clarity of the status of mixed marriage can be known.